Biomechanics of the knee. Issue 4 (August 2019) - Aweid, Osama; Osmani, Humza; Melton, Joel
Abstract: In this article the biomechanics of the tibiofemoral joint, patellofemoral joint and menisci are discussed. Normal knee kinematics depend on soft tissue and bony structures working closely together. Implant manufacturers have considered this interaction in order to design and develop a broad spectrum of total knee replacement (TKR) implant solutions. These designs include anatomic and functional considerations, asymmetric or symmetric implants, mobile or fixed bearing offerings and 'high flexion' designs, as well as designs with a single or multiple radii of curvature. Substantial differences in outcome between these designs remains unproven and TKR design selection at present is therefore often based on other factors, such as cost and the surgeon's familiarity with a particular knee system. An understanding of knee biomechanics pertaining to implant design will help surgeons with implant selection and help refine the method of implantation to optimize patient outcomes.